When virtual and material worlds collide: democratic fashion in the digital age - Crewe, Louise (Pion, 2013)
This paper explores the impact of digitally mediated communications technologies on the fashion sector. It argues that material and virtual fashion worlds are perpetually intersecting social realities that coexist relationally, simultaneously, and in mutual connection. The paper explores these shifting fashion landscapes in three particular ways in order to understand how fashion worlds are being transformed, enhanced, and reproduced in space and time. Firstly, it is argued that emergent digital technologies are remediating and refashioning existing cultural forms of signification such as fashion magazines and photography. Secondly, the potential disintermediatory effects that the Internet is having on fashion markets and consumption are explored, questioning to what extent digital technologies are enabling the devolution of fashion authority from traditional power brokers such as magazine editors and designers towards a more diversified assemblage of participants, including fashion bloggers and consumers. Thirdly, the transformative effects that digital technology is having on fashion consumption are explored. The Internet has opened up new spaces of fashion consumption that are unprecedented in their levels of ubiquity, immersion, fluidity, and interactivity. Fashion spaces are increasingly portable, must follow us around, travel with us through time and space. The network effects made possible by the Internet are enabling the creation of always-on, always-connected consumer communities. Increasingly we are adrift without the Internet, not with it. This is generating new ways of being in space where the absence of physical presence becomes second nature. Taken together, the collision between virtual and material fashion spaces requires a fundamental rethink about the role of fashion production, consumption, knowledge, and the laws of markets.